QT AS A MEANS OF CROSS-PLATFORM DEVELOPMENT - A. Lavrik; D. Kutetsky (Ìнформаційні технології в освіті)
This article observes abilities of cross-platform software development kit Qt, and compares them with abilities of Java libraries